Educational research, epistemology and the desideratum of doubt. Unpacking the complexities of the marshy divide. Issue 5 (4th July 2021) - Hennessy, Jennifer; Lynch, Raymond
ABSTRACT: Operating across the 'marshy epistemological divide' created between schooling and academia, the role of pre-service teacher researchers presents a unique set of challenges and responsibilities. This paper reports on a follow-up study exploring the attitudes of a multi-disciplinary cohort of graduand teachers towards the use and conduct of educational research at the final stages of their initial teacher education degree programme. The findings of this study highlight the impact of the epistemological swale, born within the theory practice divide, on graduand pre-service teacher researchers prior to their entry into in-career service. A widespread commitment to consensualism and crystallisation of reductionist research pre-conception is evidenced within this study. The findings of this follow-up study also provide a concomitant mapping of pre-service teacher researcher identity maturation from the point of entry onto their programme of study to graduand stage. Arising from the research findings, the authors advance the desideratum of doubt in an educational context beset with the quest for certainty and outline the need for a multi-level response to enhancing pre-service teachers' commitment to educational research across all career stages.